1992
DOI: 10.3109/00365549209052642
|View full text |Cite
|
Sign up to set email alerts
|

First Documented Case of Human Babesiosis in Sweden

Abstract: A 34-year-old splenectomized man presented with fever, myalgia and dysuria. His condition rapidly deteriorated, he became anuric and developed severe haemolytic anaemia, thrombocytopenia and fibrinolysis. Peripheral blood smears revealed intra-erythrocytic parasites consistent with Babesia divergens in 40% of the erythrocytes. The diagnosis was confirmed by gerbil inoculation and by a significant rise in antibody titer. Blood exchange transfusion reduced the number of babesia infected erythrocytes to 1%. Paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 21 publications
3
27
0
3
Order By: Relevance
“…The seroprevalence of B. divergens antibodies in our study was comparable to the results of the few other seroepidemiologic studies carried out in Europe (Uhnoo et al, 1992;Gorenflot et al, 1998;Hunfeld et al, 2002). B. divergens IgG X1:128 were found in 4.9% of the participants exposed to tick bites in Germany (Hunfeld et al, 2002), B. divergens IgG X1:40 were present in 13.3% of the patients with Lyme borreliosis in Sweden (Uhnoo et al, 1992), and B. divergens IgG X1:80 were established in 1% of the asymptomatic blood donors with tick bite in France (Gorenflot et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The seroprevalence of B. divergens antibodies in our study was comparable to the results of the few other seroepidemiologic studies carried out in Europe (Uhnoo et al, 1992;Gorenflot et al, 1998;Hunfeld et al, 2002). B. divergens IgG X1:128 were found in 4.9% of the participants exposed to tick bites in Germany (Hunfeld et al, 2002), B. divergens IgG X1:40 were present in 13.3% of the patients with Lyme borreliosis in Sweden (Uhnoo et al, 1992), and B. divergens IgG X1:80 were established in 1% of the asymptomatic blood donors with tick bite in France (Gorenflot et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…B. divergens IgG X1:128 were found in 4.9% of the participants exposed to tick bites in Germany (Hunfeld et al, 2002), B. divergens IgG X1:40 were present in 13.3% of the patients with Lyme borreliosis in Sweden (Uhnoo et al, 1992), and B. divergens IgG X1:80 were established in 1% of the asymptomatic blood donors with tick bite in France (Gorenflot et al, 1998). Because of the observed serologic cross-reactivity between Babesia EU1 and B. divergens, however, a part of the determined prevalence in our study could be attributed to the Babesia EU1, the causative agent of 3 recent human babesiosis cases in Europe (Herwaldt et al, 2003;Ha¨selbarth et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, titers of Ն1:256, possibly indicating a more recent infection with the pathogen, were found with significantly greater frequency (9 versus 1; P Ͻ 0.05) in patients exposed to ticks than in the control groups. The seroprevalences of Babesia infections in the German population examined here correlate well with those in a study of Swedish Lyme borreliosis patients, in which 13% of the individuals were found to be seropositive for B. divergens (30), and with those in a study in western France that indicated 0.5% asymptomatic seropositive individuals out of 408 investigated when a more conservative cutoff titer of Ͼ1:80 was used (A. Gorenflot, M. Marjolet, L. Hostis, A. Coutarmanac'h, and A. Marchand, Abstr. 3rd Int.…”
Section: Discussionsupporting
confidence: 81%
“…Seroepidemiological investigations from Germany, performed in healthy blood donors, show a prevalence of 1.7% (Hunfeld et al 2002). In persons with tick exposure, prevalences of 10% and 15% were determined in Germany and Sweden (Hunfeld et al 1998(Hunfeld et al , 2002Uhnoo et al 1992). These results coincide with the prevalence in ticks.…”
Section: Resultsmentioning
confidence: 86%